On the solvation in lipid bilayers measured by pyrene fluorescence: thermal and molecular composition influence on equivalent polarity in lipidic mixtures - Arrais, Dalila (2015)
Phosphatidylcholine (PC), sphingomyelin (SM) and cholesterol (CHOL) are major constituents of mammalian cell membranes. DPPC/CHOL and DPPC/DMPC are well-known binary mixtures. POPC/CHOL, DOPC/CHOL, egg-SM/CHOL, egg-SM/POPC and egg-SM/DOPC are less studied, but also important for the comprehension of the POPC/egg-SM/CHOL mixtures. These provide complex media for which polarity is hard to access. It is mainly determined by the water penetrating the bilayer (unevenly distributed creating a polarity gradient), though the influence of the dipoles from phospholipids (e.g. –PO, –CO, –OH) and the double bond in the steroid ring of CHOL cannot be neglected. CHOL derivatives are an interesting tool to verify the influence of the double bonds in the polarization of its surroundings. Pyrene fluorescence was used to access an equivalent polarity (associated to the dielectric constant) near the lipid/water interface of lipid bilayers. POPC/CHOL and DOPC/CHOL have similar thermal behavior and variation with CHOL content, though for lower CHOL content the equivalent polarity is higher for the DOPC/CHOL mixtures. The studies with DPPC and DMPC showed that pyrene does not seem to have a marked preference for either ordered or disordered phases. For DPPC/CHOL and egg-SM/CHOL the highlight goes to the behavior of the mixtures at higher CHOL amounts, where there is a substantial change in the thermal behavior and polarity values especially for the egg-SM/CHOL mixture. Egg-SM/POPC and egg-SM/DOPC show different behavior depending on which phospholipid has a higher molar proportion. The ternary mixtures analyzed do not exhibit significant differences, though there is the indication of the existence of a more ordered environment at lower temperatures and a less ordered environment for higher temperatures. The presence of 7DHC or DCHOL in egg-SM bilayers showed a tendency for the same behavior detected upon mixing higher amounts of CHOL.